SLC38A1 and STX11 are mitochondria-related biomarkers associated with immune infiltration in osteoarthritis - Lv, Wenxue; Yu, Mingxiu; Yan, Wenhai; Cai, Yuli; Wang, Weiguo (Frontiers in Genetics, 2025)
BackgroundMitochondrial dynamics and mitophagy play crucial roles in osteoarthritis (OA); however, the specific contributions of mitochondrial dynamics-related genes (MD-RGs) and mitophagy-related genes (MP-RGs) remain unclear. This study aimed to elucidate the precise mechanisms linking these genes in the context of OA.MethodsOA-related transcriptome datasets and single-cell RNA sequencing (scRNA-seq) dataset incorporating MD-RGs and MP-RGs were utilized in this study. Hub genes were identified through differential expression analysis, weighted gene co-expression network analysis (WGCNA), and machine learning. A nomogram was then constructed based on the hub genes. Enrichment and immune infiltration analyses were performed on the hub genes, and key cell types were identified based on hub gene expression. Finally, the expression of the hub genes was validated using reverse transcription-quantitative polymerase chain reaction (RT-qPCR).ResultsSLC38A1 and STX11 were identified as hub genes linked to mitochondrial dynamics and mitophagy in OA. These genes enabled the construction of a reliable nomogram for predicting OA risk. Enrichment analysis revealed that the top biological processes converged on the ECM–receptor interaction, underscoring its critical role in OA pathogenesis. Immune infiltration analysis uncovered significant disparities in 10 immune cell types, including activated CD4 T cells and central memory CD4 T cells, between OA patients and healthy controls. The levels of these immune cells were strongly correlated with the expression of SLC38A1 and STX11. Additionally, endothelial cells, monocytes, and T cells emerged as key cellular players in OA. RT-qPCR validation showed that SLC38A1 was significantly downregulated in OA samples, and STX11 exhibited a similar trend, suggesting their potential roles in OA progression.ConclusionThis study identified SLC38A1 and STX11 as key genes linked to mitochondrial dynamics and mitophagy in OA. These findings provide a theoretical basis and valuable reference for the diagnosis and treatment of OA.